The archimedean skepticism and the ethical crusade of Ronald Dworkin - Ramírez Avilés, Eiffel (2021)
In this text you can see the debate between the American Philosopher Ronald Dworkin and the so called by him archimedean skepticism, which is a kind of ethical skepticism. In that way, we will see first which was the beginning of ethical skepticism in the history of Philosophy, and how was its development through three summits. In the last summit, we will examine the moral error theory of the famous skeptic of Twenty Century, John Leslie Mackie, whom Dworkin wants to oppose philosophically. Finally, we will show the decisive contribution of Ronald Dworkin to the Philosophy of Ethics: the utilization of Hume’s Law as refutation of ethical skepticism.